Korelasi Indeks Massa Tubuh Ibu Hamil Dengan Pre Eklamsia Di RSUD Margono Soekarjo Purwokerto - Sumarni Sumarni; Fitria Prabandari (STIKes Ibnu Sina Ajibarang, 2023)
Preeclampsia is ranked second as a direct cause of maternal mortality. Preeclampsia has a significant correlation with the height of the body mass index of pregnant women. Body mass index is a simple formula for determining nutritional status, especially with regard to excess and underweight. The purpose of this study was to determine the correlation between the body mass index of pregnant women and pre-eclampsia. The research method used was observational analytic with a cross sectional approach. The population of this study were pregnant women with preeclampsia and pregnant women who were not preeclampsia. The sampling technique was simple random sampling. The sample size was determined using the G*Power application with a sample size of 153. The data analysis used was the Kolmorgorov Smirnov test, with a significance degree of P<0.05. The results showed that most pregnant women had a body mass index in the overweight category of 69.9%, most pregnant women had pre-eclampsia by 51% and there was a relationship between body mass index and pre-eclampsia with a value of p = 0.007. The conclusion: there was a significant correlation between the body mass index of pregnant women and pre-eclampsia.